Effect of temperature, concentration and storage time on the survival of entomopathogenic nematodes - MOLINA-ACEVEDO, JUAN PABLO; MOINO-JR, ALCIDES; SOUSA-CAVALCANTI, RICARDO; ANDALÓ, VANESSA; APARECIDA MENDONÇA, LÚCIA (Revista Colombiana de Entomología, 2006)
Entomopathogenic nematodes (EPN) are potential agents for the control of agricultural pests. Studies to improve their survival and pathogenicity under storage conditions are necessary where factors like temperature, concentration and time determine their viability. In this experiment the percent survival of nematodes (PSN) in storage was determined for six species of EPN, three steinernematids (Rhabditida: Steinernematidae): Steinernema carpocapsae (Weiser), S. glaseri (Steiner) and S. arenarium (Artyukhovsky), and three heterorhabditids: (Rhabditida: Heterorhabditidae) Heterorhabditis bacteriophora (Poinar), H. bacteriophora HP88 (Grenier) and H. baujardi LPP7 (Dolinski), at five temperatures (8, 12, 16, 20, and 24°C), two concentrations (1000 and 10000 IJ/mL) and two times (15 days and 3 months). The experimental design was plots subdivided by time, with a 6 x 2 factorial design in the plot over two times, respectively, where each treatment had 10 replications. In the survival of all EPN, the three-way interaction among temperature, concentration and storage time was significant (P<0,05). In most of the steinernematids the PSN gradually increased in a wide range of temperature from 8 to 20°C, in both concentrations and in the shortest time, registering survival between 87 and 95%. On the contrary, high temperatures of 20 and 24°C, together with the low concentration and shortest time, favored a high survival of heterorhabditids, being between 78 and 92%, respectively. In this experiment it was possible to determine the specific conditions for each EPN that represent a high survival, for their use in programs of biological control and preservation with high viability in the laboratory.